(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article analyzes some aspects of the functioning of representative bodies in the constitutional and legal dimension of modern states. The analysis of the nature of representative bodies was mediated by a complex of methodology, which made it possible to identify generalized properties that are manifested in its organization. The purpose of the article is to analyze some aspects of the theory of constitutional law that have methodological significance in the process of studying representative democracy. The presented analysis is based on scientific views on the nature of democracy, the essence of the formation of representative bodies, which helps to refine the content of general categories and typology of institutions of representation. The results allow us to draw conclusions that the formation of institutions of representation has general and specific features. These are economic, political, legal and other features of a single state. The analysis of the essence of representative power has a long process of evolution, which is formed in the constitutional legislation of modern democratic states.